Middle School Teachers' Artificial Intelligence Literacy Scale (MSTAILS): A Scale Study - Akgül, Recep; Demirtaş, Zülfü (Kafkas Üniversitesi, 2026)
The aim of this study is to develop a valid and reliable measurement tool to determine teachers' Artificial Intelligence Literacy (AIL) levels. The research was conducted with middle school teachers working in the Elazığ provincial center. During the scale development process, the relevant literature was reviewed, and as a result, AIL was structured into six dimensions: knowing-understanding, application, analysis, evaluation, design, and ethics. The item pool, prepared using a five-point Likert scale, was submitted for expert opinion to ensure content validity, and after the necessary adjustments, a draft form consisting of 26 items was created. Data were collected from 268 teachers for Exploratory Factor Analysis (EFA), and Confirmatory Factor Analysis (CFA) was conducted on data from 203 teachers. The KMO value was found to be .93, and the Bartlett Sphericity Test result was significant (p < .001). As a result of EFA, a structure consisting of 24 items and six factors was obtained, with a total explained variance of 77.89%. The CFA results support the model's structural validity (χ²/df = 2.11; RMSEA = .074; SRMR = .071; CFI = .90; TLI = .90). Furthermore, convergent and discriminant validity analyses revealed that AVE values for all dimensions were above .50, CR values ranged between .80 and .93, and CR values were greater than AVE. The fact that MSV and ASV values were smaller than AVE indicates that the dimensions are distinguishable from one another. The Cronbach's Alpha coefficient analysis, calculated as part of the scale's reliability analysis, revealed that the scale possesses high internal consistency both for its dimensions and for the scale as a whole.
Keywords: Artificial intelligence literacy; scale development; validity and reliability; factor analysis